The Influence of Work Discipline and Work Enthusiasm on Employee Performance At The Office of The Employment Social Security Organizing Agency (BPJS) of Palopo City - Nurafni Sofyan; Suparni Sampetan; Andi Rizkiyah Hasbi (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study was conducted to investigate the impact of discipline and work motivation on employee performance at the Palopo City Social Security Agency (BPJS) office. The research method used is quantitative type with descriptive and analytical approach. The research sample included all employees of BPJS Palopo City consisting of 36 individuals. Information collection was carried out using a verified questionnaire and information analysis was carried out through multiple linear regression with the help of the SPSS program. The results indicate that discipline at work and work motivation have a good and meaningful impact on staff performance, both separately and together. The coefficient of determination of 71.8% indicates that the independent variables contribute significantly to the improvement of staff performance while the others are influenced by other elements outside this study. This study emphasizes the importance of discipline and work motivation to improve efficiency and productivity in an organization.